2017
DOI: 10.3201/eid2311.170998
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma genitalium Infection in Adults Reporting Sexual Contact with Infected Partners, Australia, 2008–2016

Abstract: Data on the likelihood of Mycoplasma genitalium infection in sexual contacts, particularly for men who have sex with men (MSM), are needed to form an evidence base for guidelines. We conducted a cross-sectional analysis of patients attending a sexual health clinic in Melbourne, Victoria, Australia, during 2008–2016. We calculated the proportion of contacts with M. genitalium infection and determined factors associated with infection. Among those patients reporting sexual contact with an M. genitalium–infected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 32 publications
2
20
0
Order By: Relevance
“…Furthermore, the study showed that MSW and bisexual men had a similar prevalence of urethral MG infection, much higher when compared with MSM with no female sexual partners. Several studies have reported that urethral MG infection is more associated with unprotected vaginal sex rather than anal sex 28 29. Behavioural patterns, but also a better environment for MG fitness in vagina, resulting in higher bacterial loads, could explain this fact.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the study showed that MSW and bisexual men had a similar prevalence of urethral MG infection, much higher when compared with MSM with no female sexual partners. Several studies have reported that urethral MG infection is more associated with unprotected vaginal sex rather than anal sex 28 29. Behavioural patterns, but also a better environment for MG fitness in vagina, resulting in higher bacterial loads, could explain this fact.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis, including five studies mostly testing urine, estimated the prevalence of Mgen in MSM in the community at 3.2% (95% CI 2.1 to 5.1) at any site 2. Studies have shown Mgen to be most commonly detected in the rectum of MSM, with 40.7% of contacts of the infection positive in the rectal sites 17. Mgen was detected in 7% of rectal samples from asymptomatic MSM in a recent study of 1001 asymptomatic MSM at MSHC,4 and 9% of consecutive asymptomatic and symptomatic anorectal samples from 505 MSM in Sydney 3.…”
Section: Discussionmentioning
confidence: 99%
“…genitalium infection from an M. genitalium -positive partner has been demonstrated in 48.2 % of women, 31 % of heterosexual men and 41.7 % of MSM in a cross-sectional analysis of patients attending a Melbourne sexual health clinic with symptoms [14, 67]. Current guidance recommends [65, 66] testing and treating only current partners in order to prevent re-infection of the index case [68, 69].…”
Section: Clinical Featuresmentioning
confidence: 99%